Paroxysmal Explosions, Lava Fountains and Ash Plumes at Etna Volcano: Eruptive Processes and Hazard Implications - Calvari, Sonia; Cannavò, Flavio; Bonaccorso, Alessandro; Spampinato, Letizia; Pellegrino, Alessandra G. (Frontiers in Earth Science, 2018)
Between 2011 and 2015, 49 paroxysmal explosive episodes occurred at two of Mt Etna's five summit craters: the New South-East Crater (NSEC) and the Voragine (VOR). At the NSEC, each event was usually preceded by Strombolian activity, increasing in intensity with time, and climaxed with powerful lava fountains, often accompanied by lava overflows from the crater rim and by the development of ash plumes that spread several kilometres above and hundreds of kilometres away from the crater. In turn, the ash plume caused fallout and often disruption to airports and traffic on the motorways well beyond the area of the volcano itself, impacting the stability of buildings and caused public health issues. The four episodes at VOR were more intense and of greater magnitude compared to the NSEC events, resulting in a higher ash plume, and were produced by a deeper source region. In this paper, we examine the features of the 40 episodes occurring at the NSEC during 2011-2013, and of the 4 events at VOR in December 2015. We study these paroxysmal explosions using geophysical monitoring data, characterise the episodes, and analyse all available data statistically, with the aim of recognising the eruptive processes and extracting common parameters that may prove useful for hazard assessment and risk mitigation.